Performance of broodstock and hybrid juvenile of Egyptian and sangkuriang Clarias gariepinus strains - Putri Zulfania; Muhammad Zairin Junior; , Alimuddin; Ade Sunarma (Jurnal Akuakultur Indonesia)
ABSTRACT